AquaNet – Phytoplankton from Feresjön AquaNet platform - Asa Research Station (Swedish University of Agricultural Sciences, 2024)
Phytoplankton information from grab samples taken from the AquaNet mesocosms. This data contains more specifically the number of individuals per taxonomic unit and biomass calculations.
Asa Research Station (2024). AquaNet – Phytoplankton from Feresjön AquaNet platform, 2018-07-03–2018-08-14 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/fYOMaZw1XSb62jC-RvqY_ZWg
Keywords: SITES AquaNet; Ecosystem functions; Food-web dynamics; Phytoplankton; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap